Determination of Limit Pore Size Distributions of Porous Materials From Mercury Intrusion Curves - Cieszko, Mieczysław; Kempiński, Marcin (Engineering Transactions, 2006)
The application of the capillary and chain models of pore architecture are proposed in the paper for determination of limit pore size distributions of porous materials based on the mercury intrusion curves. They estimate the range of pore sizes in the investigated material. It is proved that for a given pore size distribution, the capillary model of pore architecture, commonly used in the mercury porosimetry, and its chain model, are two limit cases of the network model of pore architecture, considered in the paper as a proper model for most real porous materials. For both limit pore architectures, the expressions describing capillary potential curves have been derived that are the basis for the procedure of determination of two limit pore size distributions. This procedure has been illustrated by determining the limit distributions for porous materials made of sintered glass beads.